An unprecedented palladium-arsenic catalytic cycle for nitriles hydration - Cirri, Damiano; Marzo, Tiziano; Pratesi, Alessandro (Frontiers in Chemistry, 2023)
An unprecedented palladium/arsenic-based catalytic cycle for the hydration of nitriles to the corresponding amides is here described. It occurs in exceptionally mild conditions such as neutral pH and moderate temperature (60°C). The versatility of this new catalytic cycle was tested on various nitriles from aliphatic to aromatic. Also, the effect of ring substitution with electron withdrawing and electron donating groups was investigated in the cases of aromatic nitriles, as well as the effect of potentially interferent functional groups such as hydroxy group or pyridinic nitrogen. Furthermore, a pilot study on the potential suitability of this approach for its scale-up is presented, revealing that the catalytic cycle could be potentially and quickly scaled up.